Facial anthropometric analysis of a healthy group of young Brazilian adults by means of stereophotogrammetry technique - Alvaro Augusto JUNQUEIRA JÚNIOR; Laís Valencise MAGRI; Melissa de Oliveira MELCHIOR; Ana Maria Bettoni RODRIGUES DA SILVA; Marco Antônio Moreira RODRIGUES DA SILVA
Abstract Introduction: Anthropometry is the science responsible for measuring the weight, size, and proportions of the human body, providing valuable and objective insights into how to characterize phenotypic variation and dysmorphology. Among the newer methods for facial analysis, the stereophotogrammetry technique has shown excellent results given its use of a group of fast cameras that photograph subjects from multiple angles. Objective: The aims of the present study were: (1) to analyze the facial profile of a group of healthy young Brazilian adults, between 18 and 30 years of age, (2) to define common facial values among the subjects, (3) to create a database of facial measurements of a portion of this young healthy Brazilian population to be used in future works, and (4) to test the precision and repeatability of the Vectra M3® equipment. Material and method: Sixty healthy young Brazilian adults participated in the study, 30 males and 30 females. Temporary craniometrical landmarks were performed in soft tissue, and those subjects underwent image capturing by the stereophotogrammetry technique. Thirty landmarks were used to take the measurements (in mm) of 35 distances. The equipment repeatability was tested in 20% of the sample (i.e., 12 subjects). Result: The values between the first and second acquisitions were statistically (p<0.05) similar for all 35 distances analyzed. The findings allowed the creation of a reliable database containing facial distances of a portion of the young healthy Brazilian population. In addition, the distances Tr-N, N-Sn, Ls-Sto, Sto-Li, En[r]-En[l] and Prn-Sn were not statistically different for the group of men (GM) and the group of women (GW), while the other 29 distances were significantly greater in GM. Conclusion: The technique and methods employed in the study yielded objective analyses of the facial profile of this group of healthy young Brazilian adults, and the equipment Vectra M3® showed a high level of precision and repeatability.